PERBAIKAN METODE KERJA DAN PERANCANGAN FASILITAS KERJA UNTUK MENGURANGI RESIKO MUSCULOSKELETAL DISORDERS (MSDs) (STUDI KASUS : CV. GRAFFITY LABELINDO) - Nur Rahman As’Ad; Nova Nur Azizah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
All of the production activity in a company cannot be separated with the material handling activity. There are a lot of companies that still use the traditional work system in the material handling activity, namely manual material handling systems. CV. Graffity Labelindo is one of company which conducts material handling mostly using human power, especially the material handling activities done by the lamination machine operators. This activities lifting materials about 6-15 kg from the bottom (floor) into the top, makes workers have to bent to lift the materials, and then carry the materials by hand while moving about 20-24 meters.. Based on the results of questionnaires Nordic Body Map the biggest complaint that perceived lamination machine operator found on the neck, arms, thighs, waist, and back. The methods used in this research is OWAS (Ovako Working Analysis System). According to the data processing, the result shows that almost all the material handling activity done by the lamination machine is included in the risk category 3 (three) which is positions with harmful effects on the musculoskeletal system (high risk) an require the corrective action. The corrective action done to reduce or prevent risks of musculoskeletal disorders on the operator lamination machine is designing work facilities and improvements to the working methods. The results of the improvements can lower risk category operators lamination machine into risk category 1 (one) as to its normal position without any effects that can interfere with the musculoskeletal system (low risk).